Dampak Guncangan Harga Minyak Dunia Terhadap Dinamika Inflasi di Indonesia - Rahmania, Septia Tri; Anis, Ali (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This study aims to identify and analyze the impact of world oil price shocks on inflation dynamics in Indonesia. This research is a quantitative research using secondary data with quarterly data from 1993-2022. The analysis used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: Vector Auto Regression (VAR) Analysis, Empirical Models Vector Auto Regression (VAR) Analysis, Vector Auto Regression (VAR) Analysis Steps such as: Stationarity Test, Cointegration Test, Optimum Lag, Model Stability Test, Impulse Response Function (IRF), Variance Decomposition. The results of this study indicate that (1) world oil prices have a significant influence on the dynamics of inflation in Indonesia. This means that world oil prices can affect the dynamics of inflation in Indonesia, especially in the short term. (2) Shocks to world oil prices also have an impact on aggregate demand and supply of world oil which then affect the dynamics of the national macro economy which in turn will cause changes in the inflation rate in Indonesia